Handbook of Evolutionary Research in Archaeology - Prentiss, Anna Marie (Springer, 2019)
Evolutionary archaeology has developed from a marginal discussion to a mainstream focus in modern archaeology. Archaeologists have become widely aware that the rigorous procedures developed in the guise of evolutionary research can provide significant insight into a host of phenomena including technological change, migration, subsistence adaptation, demography, sociality, and cognition on long and short scales (Lycett 2015). This handbook is designed as a guide to current research trends, insights, and contributions of evolutionary research in archaeology. The theoretical focus in all chapters is Darwinian evolution process inclusive of perspectives broadly derived from the modern evolutionary synthesis (Huxley 1942) and the emerging extended evolutionary synthesis (Laland et al. 2015). Contributions to the book are not about neoevolution and other social science paradigms more influenced by the writing of Spencer (1857; e.g. Harris (1979); White (1959)). Given the focus on archaeology, the book also excludes specific coverage of evolutionary psychology though issues of cultural transmission and cognitive archaeology at times take us into psychological realms. Finally, this is not specifically a book about paleoanthropology though the models of evolutionary archaeology, human ecology, and evolutionary cognitive archaeology offer a wide range of contributions to our understanding of human bio-cultural evolution.